A self-powered one-touch blood extraction system: a novel polymer-capped hollow microneedle integrated with a pre-vacuum actuator. Issue 2 (29th October 2014) - Li, Cheng Guo; Dangol, Manita; Lee, Chang Yeol; Jang, Mingyu; Jung, Hyungil
Abstract : A self-powered one-touch blood extraction system is fabricated by the integration of a smart polymer-capped hollow microneedle and a pre-vacuum actuator. It is well suited for integration with other microsystems to realize a real-time micro total analysis for point-of-care diagnosis. Abstract : Blood is the gold standard sample medium that can provide a wide variety of useful biological information for the diagnosis of various diseases. For portable point-of-care diagnosis, blood extraction systems have attracted attention as easier, safer, and more rapid methods of collecting small blood volumes. In this paper, we introduce a novel self-powered one-touch blood extraction system created by assembling a smart polymer-capped hollow microneedle in a pre-vacuum polydimethylsiloxane actuator. The optimized hollow microneedle was precisely fabricated by drawing lithography for minimally invasive blood extraction, with a length of 1800 μm, an inner diameter of 60 μm, an outer diameter of 130 μm, and a bevel angle of 15°. The system utilizes only a single step for operation; a finger press activates the blood sampling process based on the negative pressure-driven force built into the pre-vacuum activated actuator. A sufficient volume of blood (31.3 ± 2.0 μl) was successfully extracted from a rabbit for evaluation using a micro total analysis system. The entire system was made of low-cost and disposable materials to achieve easy operation with a miniature structure and to meet the challenging requirements for single-use application in a point-of-care system without the use of any external power equipment.